Surveilans Aedes aegypti Menggunakan Ovitrap di Desa Endemis Demam Berdarah Kabupaten Banyumas - Juli Rochmijati Wuliandari; Dini Siswani Mulia; Susanto Susanto (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Entomological surveillance is essential to evaluate the abundance and distribution of Aedes aegypti mosquito, the dengue virus’s primary vector. This study investigates the abundance and distribution of Aedes spp collected with ovitraps in Mersi and Ledug, Purwokerto Timur, Banyumas. Both localities are identified as dengue endemic areas by the Banyumas’ Health Service. Ovitrap surveillances were performed every two weeks in Mersi and Ledug, in January – March 2022. For each localitiy, 50 respondent houses were randomly selected and 5 ovitrap surveillance trips were conducted. In each trip, 100 ovitraps were distributed to 50 respondent houses. At every single house, one ovitrap was placed inside the house (indoor) and one outside the house (outdoor). All samples collected were transported to and reared at Zoology laboratory, UMP. Mosquito larvae were identified to species at instar IV and totaled. The OPI (Ovitrap positivity index) for both indoor and outdoor ranged from 38,00% - 59,70%. The mean number of larvae for Mersi outdoor (612,50±109,73) was higher than Mersi indoor (478,80±42,96) p= .031 and Ledug indoor (347,20±45,04) p= .000, but not significantly different from Ledug outdoor (507,20±51,07) p= .109. There was no significant difference for EDI (egg density index) in the four ovitrap placements, F(3,16) = 1.132, p= .366. However, the MNE (mean number of eggs) showed a significant difference for Mersi and Ledug both indoor and outdoor F(3,16) = 14.528, p= .000. Conclusion: The OPI showed that the distribution of Aedes spp in Mersi and Ledug was high. Ae. aegypti and Ae. albopictus were found as both outdoor and indoor breeder although Ae. aegypti was found to be the dominant both as indoor and outdoor breeder.